THE CORRELATION BETWEEN PLACENTAL LOCATION AND EARLY DETECTION OF FETAL GENDER - Raghad Luay Maatoq; Sarab Salih Jasim (Western European Studies, 2024)
This is a cross-sectional study was conducted from 1st of October 2023 to 30th June 2024. A convenient sample of 50 pregnant women who attend the obstetrical and gynecology clinics in Tikrit Teaching Hospital. Inclusion Criteria include: Single viable fetus with gestational age range 5-7 weeks. The exclusion Criteria include: multiple pregnancies, abortion, bicornate uterus, fetal death, and reluctance to participate in the study. The placental site at right side was significantly higher among male sex 14(70%) in comparison to 10(33.3%) of the female sex, while the female sex was commonly on the left side 20 (66.7%) in comparison to male 6(30%). The placental site anteriorly was non significantly higher among female sex 19(63.3%) in comparison to 8(40 %) of the male sex, while the male sex was commonly on the posterior side 12(60 %) in comparison to female 11(36.7 %). The placental location at Right anterior was higher among male sex 5(25%) than female sex 5(16%), Right Posterior position was higher among male sex 9(45%) than female sex 5(16%), while Left Anterior position was higher among female sex 14(46.7%) than male sex 3(15%), Left Posterior position was higher among female sex 6(20 %) than male sex 3(15%), this relation was statistically significant. The mean crown rump length among male sex at 7 week of gestation was significantly higher than female sex (10.5±0.92), (7.8± 3.6), respectively. The mean fetal heart rate among male sex at 7 week of gestation was significantly higher than female sex (148.5±2.3) ),146±2.3)respectively .
Keywords: Placental Location and Fetal Gender; Early Detection of Fetal Gender